A cross-sectional study of risk factors and hypertension among adolescent Senior High School students - Amponsem-Boateng, Cecilia; Zhang, Weidong; Bonney Oppong, Timothy; Opolot, Godfrey; Kumi Duodu Kyere, Emmanuel (Diabetes, Metabolic Syndrome and Obesity: Targets and Therapy, 2019)
Hypertension is among the first five causes of mortality, globally contributing more than 40% to cardiac related deaths worldwide, with almost 70% cardiovascular deaths in the low- and middle-income countries. Its burden is projected to be 150 million by 2025 based on epidemiological data within the Sub-Saharan Africa regions, with Ghana experiencing 505,180 increases in 2007. It is currently among the leading cause of death in the country, with prevalence ranging from 19% to 48%. There is limited data concerning hypertension on Ghanaian youth. Particularly, on those at the Senior High School (SHS) level that represents the immediate workforce of the country on the depth of prevalence, knowledge as well as the risk factors that may predispose them into having prehypertension and hypertension for proper records and interventional measures and that is what this study pursues to do. Materials and methods: A cross-sectional study was employed in five different SHSs in the Ashanti region of Ghana from December 2018 to February 2019 with structured questionnaires and physical screening of participants. Logistic regression analysis was performed to test for relation knowledge and riskfactors on HTN. Results: The overall prevalence of pre-HTN within the group was 33.8%, with stages 1 and 2 HTN prevalence of 5.4%. Sixty-three percent do not have an idea of what HTN is, and positive associations were found between no physical exercises, no addition of extra salt, type of food often eaten and family history. Conclusion: This study establishes prevalence in pre-HTN within students at the SHS level with low knowledge and high risk factors on the disease. This indication is beneficial to target the interventional programs on this population at this early stage by inculcating education on HTN prevalence and its risks in the educational curricular by the government.
Keywords: Hypertension; Hip circumference; BMI; Youth; Age; Metabolic syndrome